Computer Network Design and Network Security System Development Computers in the Age of Big Data - Dwi Fahrulrezza; Muhamad Jaky Jamal; Nova Rahmad Prasetya; Emi Sita Eriana; Fajar Haditio (International Journal of Educational and Life Sciences, 2024)
The proliferation of big data has raised new challenges in terms of network security. This research proposes a network architecture inspired by the concept of software-defined networking (SDN) to provide high flexibility and scalability in the face of exponential data growth. In addition, an artificial intelligence-based security system is developed to detect increasingly sophisticated threats. The test results show that the designed network architecture is able to improve system performance and reliability, while the security system succeeds in reducing the false detection rate and increasing the intrusion detection rate. This research is expected to serve as a foundation for the development of a more secure and efficient network infrastructure in the big data era.